Outcome Analysis of Lipomeningomyelocele Repair in Children in a Tertiary Care Center in Nepal - Koirala, Puspa R; Pradhanang, Amit B; Sedain, Gopal; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2019)
Introduction: Lipomeningomyelocele (LMM) is a common neural tube defect especially prevalent in low income countries. When they get appropriate care, long term result is generally good provided the patient receives good neurosurgical, pediatric and rehabilitation care. Surgery is the mainstay of treatment. Our aim was to analyze immediate and long-term results of lipomeningomyelocele repair in symptomatic patients presenting to TU Teaching Hospital, Kathmandu, Nepal. Methods: Thirteen patients admitted to Department of Neurosurgery from January 2017 to December 2018 were evaluated. All patients underwent MRI of whole spine before surgery. Surgical procedures involved total excision of lipoma and repair in 10 patients and subtotal excision and repair in 3 patients. Division of filum terminable could be donein 8 patients. Follow up varied from 6 months to 2 years. Results: This study included 8 (61.5 %) patients of lumbosacral LMM, 3 (23%) patients of sacral LMM and 2 (15.38%) patients of thoracolumbar LMM. About 2 (15.38%) were operated before 3 months of age, 2 (15.38%) were operated between 3-6 months of age, 5 (38.46%) were operated between 6-12 months of age and 4 (30.7%) were operated after 1 year. All children except one presented with lump on back since birth and four presented with urinary incontinence, one presented with bilateral club foot. Four (30.7%) patients had weakness of one or both lower limbs. Two (15.38%) patients had improvement in urinary incontinence, two unchanged and one had developed urinary incontinence postoperatively. Four children with had weakness of lower limbs; one patient improved whereas three patients did not improve postoperatively. There was no development of post operative hydrocephalus after LMM repair. Three (23%) patients developed wound infection who responded well with regular dressings and antibiotics. Conclusion: Lipomeningomyelocele repair can be done with satisfactory outcome with total excision of lipoma and division of filum terminale. Patients with residual diploma and undivided filum terminale should be observed closely for the development of progressive neurological deterioration.